Do Islamic Attributes, Scepticism, Halal Awareness, and Attitude Affect the Purchase Intention of Halal Food Products in Tana Toraja, Indonesia? - Sukran; Syaifullah; Ega Rusanti (Dinamis : Journal of Islamic Management and Bussiness, 2025)
This study explores the factors influencing purchase intention for halal products in Tana Toraja, focusing on Islamic attributes, scepticism, and halal awareness. The Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis method was used to test the relationship between variables. The results show that Islamic attributes contribute positively to consumer scepticism, while scepticism does not significantly affect purchase intention. Halal awareness, on the other hand, has a favorable impact on customer attitudes, which in turn influences halal product purchasing intentions. Consumer attitudes were also shown to be an important mediator in the link between halal awareness and purchase intent. The consequence is that raising consumer knowledge and comprehension of halal goods will reinforce positive consumer attitudes, boost halal food purchase intentions, and promote the expansion of the halal business in Tana Toraja, Indonesia.